Survival of Reattached Tooth: A Systematic Review (2018)
Background: The use of tooth fragment reattachment as an alternative treatment for fractured anterior teeth has been widely reported. However, there is controversy about its longevity. This necessitates the review of studies on its survival rate. Aim and objectives: To determine the reported survival rate of reattached tooth fragments and to assess the storage media, techniques and materials used for tooth reattachment as it affects the longevity of the restorations. Design of the study: This is a systematic review of studies conducted on tooth fracture reattachment. Setting: The review was carried out at the University College Hospital, Ibadan, a tertiary hospital in South-Western region of Nigeria. Materials and Method: A systematic search of PUBMED, Cochrane, Web of science, Scopus, Google scholar and Google was done three times for better outcome. Case reports, observational studies, in vivo studies, and cross sectional studies that were written in English language were included. Key words and phrases such as'tooth reattachment', 'fragment tooth reattachment', 'crown fragment reattachment' as well as 'AND' 'OR' were employed to increase the field of search. Articles downloaded were critically appraised by the two authors for inclusion. Data including authors' name, date, institution, age/gender of patient, teeth involved, medium of storage, technique of reattachment, materials used, and followup period were extracted and entered into a data proforma. Results: Search yielded 206 articles of which 61 relevant ones were downloaded and twenty five studies that met the selection criteria were analysed. A total of 29 teeth were treated in the studies. The majority, 20 (69.2%), of the patients were male and 15 (51.7%) of teeth treated were tooth-type 11. Ellis class III fracture 21 (72.4%) constituted the major indication for reattachment. Material mostly used for tooth reattachment was Light cured composite resin in 16 (55.2%) teeth followed by flowable composite in 8 (27.6%) and dual cure composite in 5 (17.2%) teeth. Follow-up period was between 3 months and 10 years with an average of 2-year-longevity and survival fate. Conclusion: Tooth reattachment as an alternative treatment for fractured anterior teeth is simple, conservative, cost effective and aesthetically pleasing with fairsurvival rate